2018
DOI: 10.1123/jsep.2018-0083
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional and Longitudinal Associations Between Athlete Burnout, Insomnia, and Polysomnographic Indices in Young Elite Athletes

Abstract: Edith and Brand, Serge (2018) Cross-sectional and longitudinal associations between athlete burnout, insomnia and polysomnographic indices in young elite athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Sleep architecture data for elite athletes were very limited in the literature (N1 and N2 are presented as data from one study). 30 To the best of our knowledge, there were no discrete data according to sleep stages for male or female elite athletes and for semi-elite female athletes ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sleep architecture data for elite athletes were very limited in the literature (N1 and N2 are presented as data from one study). 30 To the best of our knowledge, there were no discrete data according to sleep stages for male or female elite athletes and for semi-elite female athletes ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is also a possibility that change in physical activity is not linearly related to change in mental distress, although at this point this is only speculation. However, several studies have shown that adolescents who are highly involved in (competitive) strenuous physical activity are at increased risk to suffer from symptoms of burnout and depression [52, 53]. Some individuals with high positive change in physical activity levels may have higher scores on mental distress, thus, counterbalancing the possible preventive effect of physical activity on mental distress.…”
Section: Discussionmentioning
confidence: 99%
“…Beltran-Valls et al (4) found no differences in sleep quality or duration when comparing young (mean age 13.9 [0.3] y) athletes who competed regularly in organized sport events and trained ≥3 days per week with nonathletes or inactive adolescents, and Brand et al (5) found no difference in self-reported sleep duration between adolescent athletes and controls, although athletes reported better sleep quality and fewer awakenings. Interestingly, in a recent study of adolescent athletes, 4%-11% reported clinically relevant insomnia symptoms (11). The International Olympic Committee's Medical Commission recommends adequate sleep as part of a balanced lifestyle for elite child athletes (23).…”
mentioning
confidence: 99%